Time Budget Pressure and Psychological Traits as Predictors of Dysfunctional Auditor Behavior - Haslinda, Haslindah (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study investigates the influence of external locus of control, time budget pressure, and professional skepticism on dysfunctional auditor behavior in public accounting firms (KAPs) located in Makassar, Indonesia. Dysfunctional auditor behavior—such as premature sign-offs, underreporting of time, and superficial audit procedures—can undermine audit quality and threaten the integrity of financial reporting. Understanding the behavioral factors that contribute to such unethical practices is crucial for enhancing audit effectiveness. A quantitative research design was employed using primary data collected through structured questionnaires distributed to 40 auditors from various KAPs. The data were analyzed using multiple linear regression to test the relationships among variables. The results reveal that both external locus of control and time budget pressure have a positive and significant impact on dysfunctional auditor behavior. This implies that auditors who attribute outcomes to external factors or experience excessive workload and tight deadlines are more prone to compromise professional standards. Conversely, professional skepticism has a negative and significant effect, suggesting that higher levels of skepticism can reduce the likelihood of dysfunctional actions. The findings highlight the need for audit firms to strengthen professional skepticism through targeted training and to manage time pressures to reduce unethical behavior. This study offers practical implications for regulators, firms, and audit educators.